White rice eaters in Asian countries and increased risk of development type-2 diabetes mellitus: Facts to ponder (Bangladesh Journal of Medical Science, 2016)
Abstract not availableBangladesh Journal of Medical Science Vol.15(4) 2016 p.657-658